And it burns, burns, burns, the ring-of-fire: Reviewing and harmonizing terminology on wildfire management and policy - Huidobro, Gabriela (2024)
In recent decades, extreme wildfire seasons worldwide have disrupted coupled human and natural systems owing to both changing climatic conditions and inadequate land and fire management policies. Given that wildfires are expected to become more frequent, the number of relevant scientific studies has also boomed in recent years. Simultaneously, shifts in fire management approaches have resulted in the development of new policies and vice versa. Originating from diverse fields, the terminology used in research and policy communities is far from consistent, which hinders science-based, up-to-date engagement between wildfire researchers and policymakers. Hence, this study aims to harmonize the terminology on key concepts and establish a typology for systematically classifying all wildfires and management actions observed in the literature. We conducted a scoping literature review and developed a cyclical analytical framework, called the ring-of-fire, drawing on cyclical conceptions of fire management and public policy, respectively. Consequently, we propose criteria for establishing a common dialogue between wildfire actors by providing a system for classifying actions and presenting a reference system for wildfire definitions. Furthermore, we present results by geographical regions regarding fire management actions and discuss the use of the “fire suppression” concept given its ambiguity. This review highlights the importance of consistent terminology in interpreting the differences between management actions and fire types. We hope that removing linguistic uncertainty in wildfire management-related concepts will result in a more rigorous use of the terms among scientists while also clarifying their use in communication between scientists, policymakers, and the broader public.